2005
DOI: 10.1007/s00011-005-1342-0
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous coronary intervention triggers a systemic inflammatory response in patients treated for in-stent restenosis – comparison with stable and unstable angina

Abstract: We suggest that PCI triggers a systemic inflammatory response in patients with ISR and considerable differences in its pattern when compared with SA and UA patients were demonstrated. Moreover, a high preprocedural TNF-alpha level and its increase provoked by PCI in the ISR group warrant the need for further investigation of its possible involvement in the restenosis process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 39 publications
1
10
0
1
Order By: Relevance
“…An inflammatory response has been observed immediately following other cardiovascular procedures such as percutaneous coronary intervention [20], diagnostic coronary angiography [21], and cardiac surgery [22,23,24]. SIRS has also been observed following TAVI [10].…”
Section: Discussionmentioning
confidence: 99%
“…An inflammatory response has been observed immediately following other cardiovascular procedures such as percutaneous coronary intervention [20], diagnostic coronary angiography [21], and cardiac surgery [22,23,24]. SIRS has also been observed following TAVI [10].…”
Section: Discussionmentioning
confidence: 99%
“…Kozinski et al [45] did not find any significant difference in IL-10 concentrations in patients treated with PCI, whereas DominguezRodriguez et al [44] found that IL-10 levels are increased in patients with AMI treated with primary percutaneous transluminal coronary angioplasty. It has been, however, demonstrated that both systemic [9] and coronary atherosclerosis are associated with increased plasma concentrations of some inflammatory cytokines [46].…”
Section: Discussionmentioning
confidence: 97%
“…Systemic markers of inflammation are increased in patients with ACS and usually rise within 24 h to 48 h after PCI [49,50]. Cross-reactions of abciximab with integrins avb3 and Mac-1 are assumed to decrease the endothelial inflammatory reaction.…”
Section: Abciximabmentioning
confidence: 99%